2010
DOI: 10.1185/03007995.2010.532544
|View full text |Cite
|
Sign up to set email alerts
|

Excessive sleepiness: under-recognized and essential marker for sleep/wake disorder management

Abstract: ES and ES-related sleep/wake disorders are commonly encountered in the primary care setting. By providing an educational framework for primary care physicians, the SWG hopes to improve patient outcomes by emphasizing recognition, prompt diagnosis, and appropriate ongoing management of ES and associated sleep/wake disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 91 publications
0
10
0
1
Order By: Relevance
“…Indeed, the prevalence of obstructive sleep apnoea syndrome is lower in our study than in previous general population studies which have employed more definitive diagnostic methods [11,12]. It seems likely therefore that some patients with obstructive sleep apnoea syndrome will have gone unrecognised altogether [13,14,43] although it is also possible that some may have been misdiagnosed as having another sleep problem, in which case they would have been classified firstly as “any sleep problem” and then as a “sleep problems other than sleep apnoea” in this study. However, previous studies indicate that a diagnosis of obstructive sleep apnoea made by a general practitioner is usually correct [14,44].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Indeed, the prevalence of obstructive sleep apnoea syndrome is lower in our study than in previous general population studies which have employed more definitive diagnostic methods [11,12]. It seems likely therefore that some patients with obstructive sleep apnoea syndrome will have gone unrecognised altogether [13,14,43] although it is also possible that some may have been misdiagnosed as having another sleep problem, in which case they would have been classified firstly as “any sleep problem” and then as a “sleep problems other than sleep apnoea” in this study. However, previous studies indicate that a diagnosis of obstructive sleep apnoea made by a general practitioner is usually correct [14,44].…”
Section: Discussionmentioning
confidence: 54%
“…However, primary care consultation records have been widely used in gout research [1,2,41,42] and, although not undertaken during the current analysis, in a previous study undertaken using consultation data from the CiPCA database, scrutiny of consultation free text recorded by general practitioners confirmed features of inflammation and distribution of affected joints generally consistent with a diagnosis of gout [34]. Diagnosis in primary care is also an important consideration for obstructive sleep apnoea syndrome which is frequently unrecognized [14,43]. Indeed, the prevalence of obstructive sleep apnoea syndrome is lower in our study than in previous general population studies which have employed more definitive diagnostic methods [11,12].…”
Section: Discussionmentioning
confidence: 91%
“…Several clinical trials have shown the ability of oral and intravenous bisphosphonates to reduce the incidence and frequency of SREs and skeletal morbidity and prevent bone loss in patients with breast cancer bone metastasis when administrated alone or in combination with adjuvant therapy (5,1924). However, results from the recent AZURE (4) trial, in which over 3000 patients with stage II/III breast cancer were randomized to receive standard therapy (chemotherapy, endocrine therapy, radiation) or standard therapy plus 4 mg of ZOL showed no significant difference between patients receiving ZOL in addition to adjuvant therapy compared to patients receiving only standard therapy, in terms of recurrence of breast cancer or on overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic complications of bone metastasis can have devastating effects and patients experience debilitating skeletal-related events (SREs), including pathological fractures, hypercalcaemia of malignancy and spinal cord compression. SREs are accompanied by severe bone pain and loss of mobility, which eventually leads to reduction of quality of life and survival (35). …”
Section: Introductionmentioning
confidence: 99%
“…Nocturia is often not considered among the common sleep problems, but it may have deleterious effects on both sleep and quality of life (20), which was not assessed in this study. Inadequate sleep and excess sleepiness are similarly under-recognized (21) and detrimental to physical and mental health.…”
Section: Discussionmentioning
confidence: 99%